Synthesis and crystal chemistry of the hybrid perovskite (CH3NH3)PbI3 for solid-state sensitised solar cell applications - Baikie, Tom (2013)
The hybrid organic–inorganic perovskite (CH3NH3)PbI3 may find application in next generation solid-state sensitised solar cells. Although this material and related perovskites were discovered many decades ago, questions remain concerning their diverse structural chemistry and unusual properties. The article presents a review of previous work and provides a detailed description of the preparation, structural characterisation and physical characteristics of (CH3NH3)PbI3. The phase changes exhibited by (CH3NH3)PbI3 have been probed using variable temperature powder and single crystal X-ray diffraction, combined with differential scanning calorimetry, thermogravimetric analysis and phase contrast transmission electron microscopy. The optical band gap for (CH3NH3)PbI3 determined by UV-Visible spectroscopy was compared to values obtained from density-of-state simulation of the electronic band structure.